A Rāma temple in 19th century Nepal: history and architecture of the Rāmacandra temple in Battīsputalī, Kathmandu - Michaels, Axel (Publications of the Nepal Research Centre, 1995)
Contributed articles by a group of students from the Institute for the Comparative Study of Religions of the University of Bern, Switzerland, after a trip to Nepal in 1994
Literaturverz. S. 79 - 81
Keywords: Rāmacandra Temple (Kathmandu, Nepal); Geschichte; Rāmacandra-Tempel Battīsputalī